640 Effect of long-term exposure to asbestos on functional properties of human cd8+t cell line. (24th April 2018) - Kumagai-Takei, N; Nishimura, Y; Matsuzaki, H; Lee, S; Yoshitome, K; Otsuki, T
Abstract : Introduction: The tumorigenicity of asbestos, which is thought to cause mesothelioma, has been clarified, whereas its effect on anti-tumour immunity remains unclear. In ICOH Congress 2015, we have reported the enhanced decrease in% perforin + cells of stimulated CD8 + cells of the patients with malignant mesothelioma (MM). This result suggest the decrease in stimulation-induced cytotoxicity in MM patients. Therefore, we hypothesised that chronic exposure to asbestos might affect anti-tumour immunity of CTL, and examined this possibility by comparing long-term cultures of human CD8 + T cell line EBT-8 between with and without exposure to chrysotile (CH) asbestos as an in vitro model to analyse the effects of exposure on CTL. Methods: EBT-8 cells were continuously cultured with CH asbestos at 0, 5, or 30 μg/ml, and were designated EBT-8-Org, EBT-8-CH5, and EBT-8-CH30, respectively. The cells were regularly separated from asbestos using a Ficoll-Hypaque density gradient, before being assayed for MFI of granzyme B and percentage of perforin + cells by flow cytometry. The cells were also stimulated with PMA/ionomycin for 4 hour or beads coated with anti CD3 Ab for 48 hour and assayed for IFN-λ production by flow cytometry and ELISA, respectively. Result: The long-term exposure to CH asbestos at 5 μg/ml or 30 μg/ml did not suppress the MFI of granzyme B in EBT-8 cells. In contrast, both the doses of CH exposure suppressed the percentage of perforin + cells. Although the exposure to CH did not suppress intracellular level of IFN-λ induced by PMA/ionomycin, the secreted production of IFN-λ stimulated via CD3 decreased by CH exposure. Discussion: These results indicate that long-term exposure to asbestos has the potential to suppress the perforin level and the production of IFN-λ of human CD8 + T cells. Further study is needed to clarify the mechanism of asbestos-caused suppressed function of CTL.